SARS-CoV-2 infection in adults and HIV: an update - Dimitrios Bousis; Francesk Mulita; Ioanna Marlafeka; Themistoklis Paraskevas; Dimitrios Velissaris (Medicinski glasnik, 2022)
Aim: COVID-19 pandemic caused by SARS-CoV-2 is spreading throughout the world affecting both healthy individuals and people with underlying immune-deficiencies. People living with human immunodeficiency virus (HIV) consist a group multiply affected by this universal crisis. Methods: Literature search aiming to identify relevant publications referring to the consequences of the COVID-19 pandemic in HIV infected population. Results: A body of literature is rapidly growing in regard to epidemiological data, the interaction between HIV and SARS-CoV-2, and clinical outcome in people living with HIV. Intensive research is warranted to identify any interactions of the co-existence of the two viruses in the immune system of HIV infected patients as common pathophysiology and molecular aspects are recognized. Human relations are diminished as a result of the social measures, and detailed recording of the consequences in this population is needed. Conclusion: Further research could shed light on the common underlying molecular mechanisms of both conditions in an attempt to discover treatment regimens for SARS-CoV-2 infection.
Keywords: AIDS; COVID-19; pandemic